Gender Ideology and the Rise of La Libertad Avanza in Argentina. 100 days of Government - Berdondini, Mariana (2024)
This article analyzes the place and singularity of gender representations in the rise of Javier Milei and La Libertad Avanza (LLA) as a disruptive force on the Argentinean scene and in the diverse arc of the regional and international radical right. It begins temporally with the parliamentary debate on the legalization of abortion, around 2018 and 2020, continues with the consolidation of a radical right that is configured around the so-called “gender ideology” and describes the first three months of LLA's government. Javier Milei's irruption into Argentine politics is overwhelming in his rise and arrival at the presidency as an outsider. Also in the radical nature of his discourses and policies, the libertarian experience connotes the performativity of the association between gender ideology and cultural Marxism from a specificity that he places in Argentine history as the “caste model” and links the State as a problematic issue.